SARS-CoV-2 ORF8 Forms Intracellular Aggregates and Inhibits IFNγ-Induced Antiviral Gene Expression in Human Lung Epithelial Cells - Geng, Hua; Subramanian, Saravanan; Wu, Longtao; Bu, Heng-Fu; Wang, Xiao; Du, Chao; De Plaen, Isabelle G.; Tan, Xiao-Di (Frontiers in Immunology, 2021)
Infection with the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19, a disease that involves significant lung tissue damage. How SARS-CoV-2 infection leads to lung injury remains elusive. The open reading frame 8 (ORF8) protein of SARS-CoV-2 (ORF8SARS-CoV-2) is a unique accessory protein, yet little is known about its cellular function. We examined the cellular distribution of ORF8SARS-CoV-2 and its role in the regulation of human lung epithelial cell proliferation and antiviral immunity. Using live imaging and immunofluorescent staining analyses, we found that ectopically expressed ORF8SARS-CoV-2 forms aggregates in the cytosol and nuclear compartments of lung epithelial cells. Using in silico bioinformatic analysis, we found that ORF8SARS-CoV-2 possesses an intrinsic aggregation characteristic at its N-terminal residues 1-18. Cell culture did not reveal any effects of ORF8SARS-CoV-2 expression on lung epithelial cell proliferation and cell cycle progression, suggesting that ORF8SARS-CoV-2 aggregates do not affect these cellular processes. Interestingly, ectopic expression of ORF8SARS-CoV-2 in lung epithelial cells suppressed basal expression of several antiviral molecules, including DHX58, ZBP1, MX1, and MX2. In addition, expression of ORF8SARS-CoV-2 attenuated the induction of antiviral molecules by IFNγ but not by IFNβ in lung epithelial cells. Taken together, ORF8SARS-CoV-2 is a unique viral accessory protein which forms aggregates when expressing in lung epithelial cells. It potently inhibits the expression of lung cellular anti-viral proteins at baseline and in response to IFNγ in lung epithelial cells, which may facilitate SARS-CoV-2 escape from the host antiviral innate immune response during early viral infection. In addition, it seems that formation of ORF8SARS-CoV-2 aggregate is independent from the viral infection. Thus, it would be interesting to examine whether any COVID patients exhibit persistent ORF8 SARS-CoV-2 expression after recovering from SARS-CoV-2 infection. If so, the pathogenic effect of prolonged ORF8SARS-CoV-2 expression should be determined in the future.